The NIM Sr Optical Lattice Clock. (June 2016) - Lin, Y; Wang, Q; Li, Y; Meng, F; Lin, B; Zang, E; Sun, Z; Fang, F; Li, T; Fang, Z
Abstract: A 87 Sr optical lattice clock is built at the National Institute of Metrology (NIM) of China. The atoms undergo two stages of laser cooling before being loaded into a horizontal optical lattice at the magic wavelength of 813 nm. After being interrogated by a narrow linewidth 698 nm clock laser pulse, the normalized excitation rate is measured to get the frequency error, which is then used to lock the clock laser to the ultra-narrow 1 S0 - 3 P0 clock transition. The total systematic uncertainty of the clock is evaluated to be 2.3 × 10 -16, and the absolute frequency of the clock is measured to be 429 228 004 229 873.7(1.4) Hz with reference to the NIM5 cesium fountain.